Penanaman Karakter Kedisiplinan Siswa Melalui Pembelajaran Futsal Di Mi Al Jhaq - Sumantri, Ajis; Syaputra, Roni; Andesta, Yulva (Jurnal Dehasen Untuk Negeri, 2025)
Instilling disciplined character in students is a fundamental step in forming responsible individuals, obeying rules, and being able to manage time effectively. Physical education, especially through futsal learning, is one of the strategic means in internalizing disciplined values ​​in a fun and contextual way. The Student Creativity Program (PKM) aims to design and implement a futsal learning strategy that is integrated with the instillation of disciplined values ​​for MI Al Jhaq students. The activity methods include basic futsal technique training sessions, character value guidance, and evaluation of student attitudes during the process. The observation results showed a significant increase in four indicators of discipline, namely punctual attendance (from 56% to 90%), use of training equipment (63% to 93%), compliance with game rules (61% to 88%), and ability to follow instructions (59% to 91%). These findings strengthen that futsal learning can act as an effective medium in forming student character, especially discipline. With the support of a constructivist and participatory approach, this activity not only improves motor skills, but also forms positive attitudes and behaviors in students in a sustainable manner.